Physicochemical and Sensory Characteristics of a Chagalapoli Fruit (Ardisia compressa) Beverage Fermented Using Saccharomyces cerevisiae - Ana Flores-García; Rubén Márquez-Meléndez; Erika Salas; Guillermo Ayala-Soto; Iván Salmerón; León Hernández-Ochoa (International Journal of Food Science)
Chagalapoli fruit (Ardisia compressa) is similar to Vaccinium myrtillus (berries) with high-polyphenol content. The objective of this study was to evaluate the physicochemical properties of Chagalapoli fruit and to determine the conditions for the preparation of a fermented beverage using Saccharomyces cerevisiae yeast, evaluating the impact on sensory properties. The fermentation process lasted 4 days at 27°C, with absence of light and a fixed pH of 3.8. The phenolic contents obtained in samples were 1.27 epicatechin mg/mL in filtered juice, 1.59 epichatechin mg/mL in filtered fermented beverage, 1.91 epichatechin mg/mL in partially filtered juice and 3.19 epichatechin mg/mL in partially filtered fermented beverage. An affective test was carried out to determine the sensory acceptability of the final product, evaluating the flavor, color and aroma parameters. The fermented beverage with the greatest preference on color and flavor attributes was the partially filtered fermented beverage.